Balanced versus unbalanced growth - Wilfred A. Ndongko (Intereconomics, 1975)
The question as to which economic sectors can play a leading role in a development process has given rise to two schools of thought. The author presents a survey of the “balanced” and “unbalanced” growth theories paying special regard to their practical applicability in the framework of international development strategies.
Keywords: 330; Development Strategy